Implikasi Hukum Penetapan Kasus Ganti Kelamin dalam Perspektif Hukum Islam - Kurniawan, Itok Dwi; Muhammad, Shalahuddien Noor (Universitas Sebelas Maret, 2023)
This research aims to explore and examine the civil law implications for individuals who are Khuntsa and have changed their identities, with a focus on the perspectives of Islamic Law and Civil Law in Indonesia. The research adopts a normative legal approach with a prescriptive nature, emphasizing the analysis of legislation and case studies. If this process is carried out and followed by a legal application to change their gender identity through the court system, and the judge approves it, there will be legal implications. Additionally, it is essential to consider religious perspectives, especially Islam. To address the issues arising from the civil law implications for Khuntsa individuals who have changed their identities based on court rulings, specific regulations governing their status and position are necessary. This is aimed at ensuring legal certainty in such cases.